A Triple Amino Acid Substitution at Position 88/94/95 in Glycoprotein GP2a of Type 1 Porcine Reproductive and Respiratory Syndrome Virus (PRRSV1) Is Responsible for Adaptation to MARC-145 Cells - Xie, Jiexiong (Viruses, 2019)
The Meat Animal Research Center-145 (MARC-145) cell line has been proven to be valuable for viral attenuation regarding vaccine development and production. Cell-adaptation is necessary for the efficient replication of porcine reproductive and respiratory syndrome virus (PRRSV) in these cells. Multiple sequence analysis revealed consistent amino acid substitutions in GP2a (V88F, M94I, F95L) of MARC-145 cell-adapted strains. To investigate the putative effect of these substitutions, mutations at either position 88, 94, 95, and their combinations were introduced into two PRRSV1 (13V091 and IVI-1173) infectious clones followed by the recovery of viable recombinants. When comparing the replication kinetics in MARC-145 cells, a strongly positive effect on the growth characteristics of the 13V091 strain (+2.1 log10) and the IVI-1173 strain (+1.7 log10) compared to wild-type (WT) virus was only observed upon triple amino acid substitution at positions 88 (V88F), 94 (M94I), and 95 (F95L) of GP2a, suggesting that the triple mutation is a determining factor in PRRSV1 adaptation to MARC-145 cells.